Flesh flies (Diptera: Sarcophagidae) from a white-sand habitat in the Brazilian Amazon, with the description of four new species - Carvalho-Filho, Fernando Da Silva; Gorayeb, Inocêncio De Sousa; Soares, Jéssica Maria Menezes; de Souza, Matheus Tavares (Zootaxa, 2018)
The white-sand enclaves in the Amazon Basin are small areas scattered through the tropical forest, with sandy and nutrient-poor soils and an unusual vegetation type. The insect fauna of this ecosystem is poorly known, especially in the eastern Amazon. The flesh fly fauna of an area of open herbaceous white-sand vegetation known as “Campo Redondo” in the municipality of Cametá, state of Pará, was surveyed, resulting in the discovery of 43 species in 11 genera representing the subfamilies Sarcophaginae and Miltogramminae. Four new species are described: Dexosarcophaga (Dexosarcophaga) campina sp. nov., Helicobia cametaensis sp. nov., Helicobia domquixote sp. nov., and Metopia fofo sp. nov. Lepidodexia (Lepidodexia) grisea Lopes and Lepidodexia (Notochaeta) setifrons (Lopes) are newly recorded from Brazil. Dexosarcophaga (Bezzisca) ampullula (Engel), D. (Dexosarcophaga) transita Townsend and Titanogrypa (Cucullomyia) larvicida (Lopes) are newly recorded from the Brazilian Amazon.